Concepts of infrared and terahertz photodetectors based on vertical graphene van der Waals and HgTe-CdHgTe heterostructures - Ryzhii, M.; Otsuji, T.; Ryzhii, V.; Aleshkin, V.; Dubinov, A.; Karasik, V.E.; Leiman, V.; Mitin, V.; Shur, M.S. (Opto-Electronics Review, 2019)
We review recently proposed concepts of infrared and terahertz photodetectors based on graphene van der Waals heterostructures and HgTe-CdHgTe quantum well heterostructures and demonstrate their potential.